A SENTIMENT ANALYSIS OF EMPLOYEE COMPETENCE IN BPR (PEOPLE'S ECONOMIC BANK) SUKABUMI - Heri Firmansyah; Slamet Sutrisno; Dana Budiman (RADJA PUBLIKA, 2025)
This study aims to analyze sentiment towards employee competency at BPR Sukabumi using a text mining approach based on sentiment analysis. Employee competency is one of the key factors in determining the effectiveness and productivity of an organization, especially in the banking sector which is highly dependent on service quality and customer trust. The data used in this study were obtained from various sources, such as internal surveys, customer reviews, and comments on social media related to BPR Sukabumi employee service. The analysis method used is sentiment analysis based on text mining with Orange software on qualitative data in the form of open responses, comments, and testimonials collected through interviews to identify patterns of public perception towards aspects of employee competency, such as communication skills, technical expertise, responsibility, and service orientation. The results of customer research and interview results show a positive view towards employee competency, with 55% satisfied responses, 35% neutral, and 10% negative. The analysis focuses on speed of service, ease of access, improvement of technical competency, and transparency of information. These findings provide important input for BPR Sukabumi management in improving employee training and development programs to strengthen the competencies needed to meet customer expectations and the challenges of the banking industry. This study provides a methodological contribution in the use of sentiment analysis for human resource evaluation in the financial services sector.